A fully-differential improved recycling folded-cascode amplifier for fast-settling switched-capacitor applications - Mohammad Yavari; Mohammadamin Mohtashamnia (Engineering Science and Technology, an International Journal)
In this paper, a fully-differential class A single-stage CMOS operational transconductance amplifier (OTA) is presented for high-speed switched-capacitor (SC) applications. The main target is to improve both large and small signal parameters in order to achieve a fast-settling performance with sufficient accuracy in SC circuits without needing more power dissipation. Several techniques including the current recycling, phase margin enhancement using high-speed current mirrors, and cross-coupled local positive feedback transistors are employed in the traditional folded-cascode amplifier (FCA) to realize a multi-path single-stage OTA with increased unity-gain frequency, slew rate, and DC gain. Detailed analytical calculations and circuit level simulation results are collected to compare the suggested OTA with alternatives. Based on the analytical calculations, the proposed amplifier significantly outperforms the traditional folded-cascode OTA regarding both large-signal and small-signal parameters. The suggested OTA is simulated in TSMC 65 nm CMOS technology in a SC integrator configuration to verify its usefulness. According to the simulation results, the DC gain, unity-gain bandwidth, and slew rate of the proposed OTA are improved about 22.9 dB, 576 %, 241 %, respectively, compared to the conventional FCA with almost the same power dissipation and other similar simulation conditions. The proposed OTA can be utilized in fast-settling switched-capacitor circuits as well.